Utilization of Moringa Fruit Peel Waste and Sawdust as Hybrid Composite Boards with Polyester Resin Matrix - Leto, Kristina Tresia; Jayadin; Ridwan, Mastura; Coa, Sri Astuti Rahman; Nisa, Kartini Rahman; Mujiburohman, Muhammad; Ismiralda, Ismiralda; Farizi, Zakaria Al (Mechanical Engineering Department - Semarang State Polytechnic, 2025)
Environmental damage, previously considered a local problem, has now developed into a global issue, with waste becoming an increasingly pressing issue, especially in developing countries. Inadequate waste management has the potential to cause serious impacts on environmental sustainability and human health. One type of waste that has not been optimally utilized is moringa fruit peel waste and wood sawdust. This waste often causes soil and air pollution because it is left to pile up and burned. Therefore, this study aims to develop a Hybrid composite that combines moringa fruit peel waste and wood sawdust as a reinforcing material, as well as to test the mechanical and physical properties of the resulting composite board. This study uses an experimental approach in the laboratory with variations in waste composition (15%: 5%: 80%), (20%: 10%: 70%), (25%: 15%: 60%) and a composite board thickness of 1 cm. Testing parameters include tensile tests, compression tests, and water absorption. The tensile test results show that the composition of 15% moringa fruit peel fiber and 5% wood sawdust produces the highest tensile strength of 13.622 Mpa. Compression tests showed that a composition of 20% moringa rind fiber and 10% sawdust produced the highest compressive strength of 25.527 MPa. Water absorption tests showed that a composition of 25% moringa rind fiber and 15% sawdust had the lowest, or optimal, water absorption of 1.8%.